Students’ dropout: A case study in the career of English as a Foreign Language at Universidad Técnica Nacional, San Carlos campus (2017) - González Kopper, Natalia (2022)
This single case analysis shows the results of a research from a qualitative approach. The project aimed to establish prevention strategies from the identification of the most recurrent factors associated with the students’ dropout during the first year in the career of English as a Foreign Language (ILE) at Universidad Técnica Nacional (UTN), San Carlos campus, during the year 2017. Some instruments were designed and applied to a sample of six students who dropped university in 2017, and five professors from the ILE career, San Carlos, campus. The main results show that the labor and economical aspect influences the students’ dropout. The lack of motivation is a relevant aspect when students take this decision. The study recommends conducting workshops in order to develop strategies that helpwith the dropout in the educational system.